2019
DOI: 10.1126/science.aau7285
|View full text |Cite
|
Sign up to set email alerts
|

Parallel adaptation of rabbit populations to myxoma virus

Abstract: In the 1950s the myxoma virus was released into European rabbit populations in Australia and Europe, decimating populations and resulting in the rapid evolution of resistance. We investigated the genetic basis of resistance by comparing the exomes of rabbits collected before and after the pandemic. We found a strong pattern of parallel evolution, with selection on standing genetic variation favouring the same alleles in Australia, France and the United Kingdom. Many of these changes occurred in immunity-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
137
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(146 citation statements)
references
References 56 publications
8
137
0
1
Order By: Relevance
“…1). Moreover, we found that allele reuse (repeated selection of the same haplotype, shared either via gene flow or from standing genetic variation) frequently underlies parallel adaptation between closely related lineages [29][30][31][32] , while parallelism from de-novo mutations dominates between distantly related taxa 13 . This suggests that the degree of allele reuse may be the primary mechanism behind the hypothesized divergence-dependency of parallel genome evolution, possibly reflecting either genetic (weak hybridization barriers, widespread ancestral polymorphism between closely related lineages 33 ) or ecological reasons (lower niche differentiation and geographical proximity 34,35 ).…”
Section: Introductionmentioning
confidence: 93%
“…1). Moreover, we found that allele reuse (repeated selection of the same haplotype, shared either via gene flow or from standing genetic variation) frequently underlies parallel adaptation between closely related lineages [29][30][31][32] , while parallelism from de-novo mutations dominates between distantly related taxa 13 . This suggests that the degree of allele reuse may be the primary mechanism behind the hypothesized divergence-dependency of parallel genome evolution, possibly reflecting either genetic (weak hybridization barriers, widespread ancestral polymorphism between closely related lineages 33 ) or ecological reasons (lower niche differentiation and geographical proximity 34,35 ).…”
Section: Introductionmentioning
confidence: 93%
“…; Alves et al. ). Previous research has shown that the correlation between selection coefficients of a given allele in each of two populations inhabiting different environments is expected to increase with the similarity in the direction of selection (eq.…”
mentioning
confidence: 98%
“…Several viruses, including cytomegalovirus 70 and herpesvirus 71 manipulated the CD200-CD200R pathway as a means of immune evasion. Interestingly, in one of the longest running and most in-depth studies of host-pathogen coevolution, CD200R was shown to be under selection in rabbits in response to myxoma virus biocontrol agent 72 . As DFT1 and DFT2 have been circulating in devils for more than 20 years and 5 years, respectively, it will be important to monitor CD200/R expression and the potential evolution of paired activating and inhibitory receptors in these natural disease models 73 .…”
Section: Discussionmentioning
confidence: 99%